Peran Produksi Perikanan Tangkap Dan Budidaya Sebagai Mediasi Pertumbuhan Ekonomi Indonesia: The Role of Capture and Aquaculture Production as a Mediation of Indonesia's Economic Growth - Dedi Damhudi (CV Warnak Johanna Nusantara, 2026)
Abstracts - This study examines the fisheries sector’s contribution to economic growth within a blue economy perspective by positioning fish production as a mediating mechanism. Building on a modified Solow growth framework, we test the effects of labor and capital on GDP growth, both directly and indirectly through a latent Fish Production construct (FishProd) measured by capture fisheries production and aquaculture production. Annual secondary data are sourced from the World Bank. The model is estimated using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with bootstrapping to assess path significance and mediation effects. The results show that labor has a positive and statistically significant effect on economic growth, whereas capital is not significant. FishProd exerts a positive and significant effect on growth; however, neither labor nor capital significantly predicts FishProd. The indirect (mediated) effects are insignificant, indicating that fish production does not transmit the impacts of labor or capital to growth in the tested specification. These findings suggest that policies aiming to strengthen growth through fisheries should prioritize measures that raise fish output and improve the enabling production and post-harvest ecosystem under blue economy principles.